The complete mitochondrial genome sequence of Acisoma panorpoides Rambur, 1842 (Odonate: Libellulidae) - Lingzhen Cao; Wen Hou; Chaoxing Hu (Mitochondrial DNA. Part B. Resources, 2019)
The phylogenetic relationships of dragonflies have received great attention all the time. For a better understanding the phylogenies among odonate insects, the paper presented the complete mitochondrial genome of Acisoma panorpoides based on next generation sequencing data of total genomic DNA. The total length comprised 15,249 bp and the 37 genes (2 rRNA genes, 13 protein coding genes and 22 tRNA genes). Gene content and gene arrangement were identical to other odonate mitogenomes. Phylogenetic analyses using the whole sequences of the mitochondrial genome placed A. panorpoides as a sister species to Hydrobasileus croceus in Libellulidae.